2018
DOI: 10.3390/su10093317
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Service Innovation Practices to Reduce Energy Consumption Based on Adaptive Theory

Abstract: Research on service innovation appears in several research disciplines, with important contributions in marketing, management, and operations research. The purpose of manufacturing enterprise service is to reduce energy consumption. We offer a new account based on an adaptive theory perspective. This paper investigates the relationship among three types of service innovation practices and service innovation performance in manufacturing enterprise. The study further examines environmental uncertainty as a moder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…In recent years, with the rise of the servicedominant logic, manufacturing companies have gradually extended the service sector. Yang et al (2018) argued that service innovation in manufacturing enterprises can enhance the value of enterprise services and help enterprises to retain a sustainable competitive advantage.…”
Section: Contextual Moderatorsmentioning
confidence: 99%
“…In recent years, with the rise of the servicedominant logic, manufacturing companies have gradually extended the service sector. Yang et al (2018) argued that service innovation in manufacturing enterprises can enhance the value of enterprise services and help enterprises to retain a sustainable competitive advantage.…”
Section: Contextual Moderatorsmentioning
confidence: 99%
“…Service innovation is an important business sustainable development strategy for many enterprises [26]. Service innovation mainly refers to changes in the characteristics of the service itself [20]. Tidd et al [27] indicated that the core procedure for a corporation's sustainable development is through innovative behaviors, that is, to create value from the corporation's assets by redesigning or improving the products, services, or methods in innovative ways.…”
Section: Service Innovationmentioning
confidence: 99%
“…Satisfied customers are those considered to be insensitive to price, less affected by the competitors, willing to purchase more products and services, and staying loyal for a long time [19]. Good service can enhance customer loyalty and increase the likelihood of customers buying again [20]. Kotler [21] suggested that when satisfied, customers will have the intention to make purchases again, be more willing to discuss the products of the company with others, and become loyal to the brand.…”
Section: Introductionmentioning
confidence: 99%
“…Of the 184 questionnaires distributed, 151 returned questionnaires were usable, yielding a response rate of 82%. CC was measured, using a 17-item scale, adapted from Shoniwa (2016), MT measured, using a fifteen-item scale, adapted from Mabinya (2011) , SI measured, using eighteen-item scale, adapted from Yang et al (2018) and BG measured using a nine-item scale adapted from Lotz and van der Merwe (2013).…”
Section: Data Collectionmentioning
confidence: 99%
“…In addition, mobile technology was measured, using a fifteen-item scale, adapted from Mabinya (2011). Furthermore, service innovation was measured, using eighteen-item scale, also adapted from Yang et al (2018). Moreover, business growth was measured using a nine-item scale adapted from Lotz and van der Merwe (2013) as well as Tan et al (1998).…”
Section: Measurement Instrument and Questionnaire Designmentioning
confidence: 99%